The Effect of Auditor Reporting Choice and Audit Committee Oversight on Management Financial Disclosures - Fuller, Stephen H.; Joe, Jennifer R.; Luippold, Benjamin L. (The Accounting Review, 2021)
ABSTRACT We investigate the joint effects of auditors' reporting choice and audit committee effectiveness on management disclosures about complex estimates. A new PCAOB standard requires auditors to report on Critical Audit Matters (CAMs): issues “communicated or required to be communicated to the audit committee” about accounts or disclosures that (1) “are material to the financial statements,” and (2) “involved especially challenging, subjective, or complex auditor judgment” (PCAOB 2017a, 11). Consistent with investor arguments, we find that audit committee effectiveness and more detailed CAM reporting encourage managers' disclosures of the risk underlying complex estimates. When the auditor's report is more informative about a complex estimate and the audit committee is more effective, management's related financial disclosures are more forthcoming. However, less informative auditor disclosures or more effective audit committees alone do not prompt greater management disclosure. Thus, expanded auditor reporting and more effective audit committees, together, can enhance the disclosures investors value.